Comparative analysis of special preparedness young water-slalom - Окунь, Дар’я Олександрівна (Slobozhanskyi Herald of Science and Sport, 2016)
Okun D. Purpose: to identify indicators is specially trained water-slalom aged 10–12 years. Material & Methods: methods of theoretical analysis, synthesis and synthesis of information, pedagogical control tests (tests), methods of mathematical statistics. Results: presented materials research performance technical readiness of 60 young water-slalom groups of initial training. A comparative analysis of the results and regulatory requirements, the proposed curriculum for youth sports schools. Conclusions: the results of the study suggest lagging performance testing young athletes behind the standards of the program requirements, indicating insufficient specially trained water-slaloms